Political Business Cycles and Expenditure Policies in Developing Countries - Schuknecht, Ludger (IMF Working Papers; Working Paper ;, 1994)
The paper studies empirically fiscal policies around elections in 35 developing countries. It finds that governments try to improve their reelection prospects with the help of expansionary expenditure policies. Rising fiscal deficits before elections are followed by fiscal consolidation afterwards. These cycles can be found particularly in countries which are less trade-oriented or which pursue fixed exchange rate policies. Certain IMF-supported programs (SAF/ESAF and EFF arrangements) contribute to fiscal stabilization, but they do not appear to affect the incidence of fiscal cycles. The paper concludes that policy advice and macroeconomic projections should not overlook election constraints, and political feasibility of reforms should be strengthened particularly before elections.